Strategy use of Russian pre-service TEFL university students: using a strategy inventory for program effectiveness evaluation - Zareva, Alla (International Journal of English Studies, 2013)
The focus of the present study is on identifying categories of learning strategies that are mostly used by Russian university students in an English Linguistics Program with a TEFL concentration. The more specific goal of the study is to offer a model of evaluation of the effectiveness of TEFL-oriented programs in terms of the language learning strategies their students use and recognize as pedagogically applicable to their EFL environment. To this end, two groups of students were compared on their self-reported frequency of strategy use —1st year students (n = 23), who had just entered the program, and 4th year students (n = 38), who were close to graduating from the program and entering the teaching profession. The main instrument used in the study was a version of the Strategy Inventory for Language Learning (SILL), designed by Oxford (1990). Overall, both groups showed high to medium frequency of use of all strategy categories; however, the 4th year students revealed a more finely-grained scale of strategy use priorities. The findings of the study can help curriculum designers and instructors refine the focus of their TEFL-track programs and make informed decisions about emphases and de-emphases in their students’ training.